2009
DOI: 10.1007/s11916-009-0026-9
|View full text |Cite
|
Sign up to set email alerts
|

The electrophysiology of cluster headache

Abstract: Cluster headache (CH) is a neurovascular headache disease characterized by recurrent, strictly unilateral, severe pain attacks. Despite its typical clinical features, including circadian rhythm of the attacks and ipsilateral autonomic dysfunction, the underlying pathophysiology of CH is still unclear. Electrophysiological data point to central disinhibition of the trigeminal nociceptive system as one of the key mechanisms of CH pain. Therefore, altered habituation pattern and changes within trigeminal-facial n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The trigeminal system has been broadly implicated in generating pain in different headache disorders, but the causative factors that may sensitize and/or disinhibit the trigeminal pathway may differ across conditions. Several studies have demonstrated that there is an interaction between pain mediated by the trigeminal system and photophobia.…”
Section: Photophobia In Headache Disordersmentioning
confidence: 99%
“…The trigeminal system has been broadly implicated in generating pain in different headache disorders, but the causative factors that may sensitize and/or disinhibit the trigeminal pathway may differ across conditions. Several studies have demonstrated that there is an interaction between pain mediated by the trigeminal system and photophobia.…”
Section: Photophobia In Headache Disordersmentioning
confidence: 99%
“…In addition to having a significant impact on patients’ daily life due to pain and disability, the socioeconomic burden of headaches are considerable, with a cumulative burden of $14 billion per year (3). Although the pathophysiological mechanisms involved remain partially elusive, chronic headache is believed to have a neurogenic basis (411). For example, a recent fMRI study showed that areas within the hypothalamus and brainstem, including the trigeminal system, were involved in mediating migraine (12).…”
Section: Introductionmentioning
confidence: 99%